Technické zhodnocení budovy - Chalupová, Hana (Vysoké učení technické v Brně. Fakulta stavební, 2016)
Diplomová práce předkládá postup pro výpočet hodnoty technického zhodnocení budovy vlastníka pro účetní zaevidování a zohlednění způsobu dalšího užívání budovy. V práci jsou vysvětleny pojmy související s technickým zhodnocením budovy. Praktická část se zabývá případovou studií revitalizace panelového domu, ve které je aplikovaná metodika pro technické zhodnocení.

The diploma thesis presents the procedure for calculating the value of the technical improvements of building owner for accounting registration and taking account of another way to use of the building. In this work are explained the concepts related to technical improvements of building. The practical part deals with the practical example revitalization of the block of flats in which it is applied methodology for the technical improvements.
Technical improvements of building
Keywords: Technické zhodnocení budovy; opravy; účtování technického zhodnocení a oprav; odpisy; cena revitalizace; prodejní cena.; Technical improvements of building; repairs; accounting of technical improvements and repairs; depreciation; price of revitalization; selling price.